The Effectiveness of Quizizz-Based Gamification in Improving Students' Arabic Learning Outcomes - Bayhaqi, Abdu Alghoffar; Azhari, Saefullah; Istiqomah, Nurul (Universitas Yudharta Pasuruan, 2025)
This study aims to analyze the effectiveness of using Quizizz as a learning medium in improving students’ learning outcomes and motivation in Arabic language learning. The research employed a mixed methods approach involving 30 seventh-grade students and one Arabic language teacher. Qualitative data were obtained through observation, interviews, and documentation, while quantitative data were collected through pre-tests and post-tests analyzed using descriptive statistics and paired sample t-tests. The results indicate that the implementation of Quizizz through three main stages (preparation, implementation, and evaluation) successfully increased average learning achievement by 31.5% in vocabulary, grammar, and reading comprehension. In addition, active student participation increased by 73%, learning concentration doubled, and 87% of students reported that the learning process was more engaging. The gamification features and instant feedback provided by Quizizz were proven to create a positive, competitive atmosphere and strengthen students’ intrinsic motivation. The challenges encountered include limited infrastructure, teacher readiness, and dependence on technology. This study concludes that Quizizz is an effective, innovative, and feasible learning medium for Arabic language instruction. The practical implications emphasize the need to enhance teachers’ digital literacy and provide adequate school infrastructure to support sustainable technology-based learning.